2015
DOI: 10.1038/nature16192
|View full text |Cite
|
Sign up to set email alerts
|

Functional overlap of the Arabidopsis leaf and root microbiota

Abstract: Roots and leaves of healthy plants host taxonomically structured bacterial assemblies, and members of these communities contribute to plant growth and health. We established Arabidopsis leaf- and root-derived microbiota culture collections representing the majority of bacterial species that are reproducibly detectable by culture-independent community sequencing. We found an extensive taxonomic overlap between the leaf and root microbiota. Genome drafts of 400 isolates revealed a large overlap of genome-encoded… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

43
1,011
6
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 1,078 publications
(1,111 citation statements)
references
References 45 publications
43
1,011
6
2
Order By: Relevance
“…We evaluated Snowball using 21 simulated datasets, each containing 3-9 closely related E. coli strains and one simulated dataset containing ten novel recently published Rhizobia strains (Bai et al, 2015) (Section 3.4). We recall that good performance on different strains implies good performance on different species, which is why we put the emphasis on distinguishing between closely related strains in our experiments.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We evaluated Snowball using 21 simulated datasets, each containing 3-9 closely related E. coli strains and one simulated dataset containing ten novel recently published Rhizobia strains (Bai et al, 2015) (Section 3.4). We recall that good performance on different strains implies good performance on different species, which is why we put the emphasis on distinguishing between closely related strains in our experiments.…”
Section: Resultsmentioning
confidence: 99%
“…Nonetheless, it does not require closely related reference genomes of the studied species to be available. We have assessed the performance of Snowball using 21 simulated datasets, each containing 3-9 closely related E. coli strains and one simulated dataset containing ten recently published Rhizobia strains (Bai et al, 2015), which demonstrates the capability of the Snowball assembler to assemble novel strains. We have compared our Snowball assembler to the SAT assembler, which, to our knowledge, establishes the current state of the art in gene assembly.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The bacterial community can be influencing the endophytic colonization of this strain or the host plant favored the colonization of other strains. The design of simplified microbial communities has been recently considered as a priority for harnessing the plant microbiome in sustainable agriculture [36] and this approach has been addressed in Arabidopsis [88] and in maize [67]. In this work we initiated PGP and colonization studies of a simplified community of 10 bacterial strains and initial results encourage further studies of synergistic, signaling and cooperative behavior of a multispecies consortium as well as the role of the plant genotype.…”
Section: Seedling Inoculation With a Simplified Bacterial Communitymentioning
confidence: 99%
“…Such an approach has shown that there was not only an extensive taxonomic overlap between the Arabidopsis leaf and root microbiota but also a large overlap of genome-encoded functional capabilities. [13] Finally, nucleic acid-based techniques also enable the investigation of bacterial pure cultures introduced into an environmental compartment. Sphingomonas wittichii strain RW1 for example was inoculated into soil to achieve increased pollutant degradation.…”
Section: Clinical Microbiologymentioning
confidence: 99%